Neoadjuvant Chemotherapy in Patients With Muscle-Invasive Bladder Cancer and Its Impact on Surgical Morbidity and Oncological Outcomes: A Real-World Experience - Nguyen, Thanh-Tuan; Huillard, Olivier; Dabi, Yohann; Anract, Julien; Sibony, Mathilde; Zerbib, Marc; Xylinas, Evanguelos (Frontiers in Surgery, 2018)
Objectives The purpose of this study was to investigate the impact of neoadjuvant chemotherapy (NAC) on perioperative morbidity and on oncological outcomes according to the type of chemotherapy regimen administered to patients with muscle-invasive bladder cancer (MIBC) who subsequently underwent radical cystectomy (RC). Methods Data were collected retrospectively on 40 patients with bladder urothelial carcinoma who had at least two cycles of NAC, followed by RC, from 2011 to 2015 at our institution. The outcomes evaluated were NAC toxicity, perioperative complications, cancer-specific and overall survival. Results Among these cases, 23 patients (57.5%) received methotrexate, vinblastine, doxorubicin and cisplatin (MVAC), 4 patients (10%) received gemcitabine and cisplatin (GC), and 13 patients (32.5%) received other regimes. The early and late postoperative complication rates were 35% and 12.5%. Regarding toxicity, 85% of patients had at least one side effect of NAC, but only 21.7% discontinued therapy in the MVAC group. The pathological complete response (pCR) rates for cisplatin-based regimens (MVAC and GC) and other regimens were 44.4% and 15.4%, respectively (p=0.09). The pathological partial response (pPR) rates for cisplatin-based regimens and other regimens were 66.7% and 15.4%, respectively (p=0.002). Patients treated with a cisplatin-based chemotherapy regimen had longer overall survival than those treated with other regimen (median 38.1 vs 18.4 months, p=0.01). Conclusions NAC administration was not associated with high toxicity or surgical morbidity. The pathological response rates and survival outcomes in the cisplatin-based regimens were higher than with those with non-cisplatin-based regimens. These data support the use, in patients elective to a neoadjuvant setting prior to RC for MBIC, of a cisplatin-based regimen.